The Influence Of Work Flexibility And Salary On Employee Productivity At PT Setia Tani Mandiri Mukomuko Regency - Alisa Yuliana; Ida Anggriani; Ida Ayu Made E G (Journal of Business Management, 2026)
This research investigates the critical role of human resource management policies, specifically work flexibility and salary, in determining the level of employee productivity at PT Setia Tani Mandiri, Mukomuko Regency. Given the competitive nature of the industry, maintaining high employee productivity is paramount for the company’s operational sustainability and long-term success. The study employed a quantitative research method with an associative-causal approach to test the relationship and influence between the independent variables (X1):Work flexibility (X2:Salary) and the dependent variable (Y: Employee productivity). The sample consisted of 30 employees, selected through a saturation sampling technique, and primary data was collected using structured questionnaires. Data analysis was performed using multiple linear regression analysis, including the simultaneous hypothesis test (F-Test) and partial hypothesis test (T-Test), with a significance level of α=0.05. The results of this study indicate that flexible working hours and salaries, both simultaneously and partially, have a significant effect on the productivity of employees at PT Setia Tani Mandiri in Mukomuko Regency. These results are indicated by a significance value of < 0.05. The coefficient of determination (R2 or R Square) is 97%. The remaining 3% is influenced by other factors outside the scope of this research model.